2009
DOI: 10.1148/radiol.2533090457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Internal Derangement of the Knee at 3.0-T MR Imaging: 3D Isotropic Intermediate-weighted versus 2D Sequences

Abstract: The performance of 3D isotropic fast SE intermediate-weighted MR imaging with MPR was not significantly different from that of 2D MR imaging in the diagnosis of cruciate ligament and meniscal tears of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 38 publications
3
92
0
2
Order By: Relevance
“…18 Previous studies have reported that 3D VISTA is comparable or superior to 2D FSE for the evaluation of the nerve root in the cervical spine and that it has high sensitivity and specificity in the evaluation of meniscal tears and the ACL. 18,20,21 Park et al 13 reported that the SNRs and CNRs are higher for 3D VISTA than for 2D FSE in their study on the anterior talofibular ligament (ATFL) of the ankle joint. In the current study, the mean SNR of the PCL was lower on 3D VISTA than on 2D FSE, whereas the mean CNR was higher for 3D VISTA than for 2D FSE.…”
Section: Resultsmentioning
confidence: 99%
“…18 Previous studies have reported that 3D VISTA is comparable or superior to 2D FSE for the evaluation of the nerve root in the cervical spine and that it has high sensitivity and specificity in the evaluation of meniscal tears and the ACL. 18,20,21 Park et al 13 reported that the SNRs and CNRs are higher for 3D VISTA than for 2D FSE in their study on the anterior talofibular ligament (ATFL) of the ankle joint. In the current study, the mean SNR of the PCL was lower on 3D VISTA than on 2D FSE, whereas the mean CNR was higher for 3D VISTA than for 2D FSE.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Rubin et al reported a fall in diagnostic specificity for ligamental tears with multiple ligament injuries [7]. Magnetic resonance (MR) imaging is sensitive and specific in the diagnosis of internal derangements of the knee [8] [9]. In our study of Internal Derangement of Knee, we studied 120 patients of which 48 were left knee joint and 72 were right knee joint.…”
Section: Discussionmentioning
confidence: 97%
“…Yoon et al [14] performed TSE PDW MRI with 1 mm thickness and observed inadequate tissue contrast because of the presence of a certain degree of image degradation during the multiplanar reconstruction process owing to nonisotropic images. Jung et al [22] acquired isotropic axial multiplanar reconstruction images by 3 T MRI. However, 3D volume techniques have some limitations, such as the presence of a higher signal intensity in normal menisci than that on the spin-echo sequence and more widespread signal increase in the degenerated menisci [4].…”
Section: Discussionmentioning
confidence: 99%